Recurrence hernia in the broad ligament of the uterus: a case report - Yoshifumi Hashimoto; Tatsuo Kanda; Tadasu Chida; Kazuyoshi Suda (Surgical Case Reports)
Abstract Background Bowel herniation through a defect in the broad ligament of the uterus is a rare disease and few cases of recurrence have been reported. We report herein a recurrence case of a patient with broad ligament hernia (BLH), along with a review of the literature. Case presentation A 53-year-old woman complaining of abdominal pain was transported to our hospital. She had a history of laparotomy for small-bowel obstruction associated with hernia in the broad ligament of the uterus 10 years ago at a local hospital. Abdominal pelvic contrast-enhanced computed tomography revealed that the mesentery of the dilated bowels converged at a thick band in the pelvis, suggesting closed loop obstruction of the small bowel. The patient underwent urgent laparotomy and was diagnosed with bowel herniation through an opening in the broad ligament of the uterus on the right side, which was ipsilateral with the previous surgery. The hernia orifice was widened by incision and incarcerated bowel segments were released and preserved because ischemia was reversible. The membranous defect of BLH was closed by suture with braded silk strings. Conclusions Although BLH is a rare disease, patients face a significant risk of disease recurrence. Nonabsorbable suture may be advisable for closure of the hernia orifice in BLH.